PEMBELAJARAN BERBASIS HUMANIS RELIGIUS PADA ANAK USIA DINI: PEMBELAJARAN BERBASIS HUMANIS RELIGIUS PADA ANAK USIA DINI - Rohmah, Liatul (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
This article discusses a religious humanist-based learning. Learning is an activity carried out by a teacher, lecturer, tutor, facilitator so that students can learn. The teacher as an important key in learning because the teacher besides being an educator, also as a teacher, guide and trainer. That requires learning that can be enjoyed by students or children. One of them is religious humanist based learning. Religious humanists are a way of teaching that includes students with dignity and students according to their respective characteristics. Religious humanist learning is a process of teaching and learning in class that respects the basic values ​​to achieve success that is truly made the foundation in the formation of the morals of the nation's children. Learning students or children more enjoy learning but also does not carry the character or aspects of religion. So aspects of growth and development, such as physical, cognitive, social, emotional, linguistic aspects and other aspects such as religion and morals, independence and art can grow and develop optimally.